The Effect of Liquidity, Solvability and Profitability Ratios on Disclosure of Islamic Social Reporting In Indonesian Islamic Banking During The Period 2015-2017 - Ahmad Romli; Rahma Yudi Astuti (University of Darussalam Gontor, 2019)
Abstract: An Increase of Islamic Banking in Indonesia is very significant but its development needs to be dominated well. So Islamic economy in future can be recognized by the community and the world. First, the need for better applicability to indicate the system used is in accordance with the Islamic Shari'a system. It’s because other Islamic banking uses an annual report in accordance with the Global Reporting Initiative conventional.This study aimed to determine the effect of Islamic Social Reporting that will be associated premises in various financial ratios such as liquidity, solvability, and profitability ratios. The method used was multiple linear regression with the classical assumption. The data used were secondary data time series during 2015-2017 obtained from the annual reports of Islamic banks with sample of 12 Islamic Banks. Data processing was performed using the IBM SPSS calculation tool 25.The result data processing showed that the Islamic social reporting did support in individual variable and had an effect simultaneously. However, there were indicators that affected in variable and had good effects in.Keywords: Islamic Social Reporting, Liquidity Ratios, Solvability Ratios, and Profitability Ratios.